2003
DOI: 10.1086/375596
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Enterobacter Meningitis: Risk Factors, Management, and Treatment Outcomes

Abstract: Enterobacter species are increasingly a cause of nosocomial meningitis among neurosurgery patients, but risk factors for these infections are not well defined. A review of all adult patients hospitalized at the University of California-Los Angeles (UCLA) Medical Center during an 8-year period identified 15 postneurosurgical cases of Enterobacter meningitis (EM). Cure was achieved in 14 cases (93%), and efficacy was similar for carbapenem- and cephalosporin-based treatment. A matched case-control study comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Likewise, Enterobacter species have been reported to cause disease in poultry (Nandi et al, 2013), it has also been isolated form egg shell of poultry together with other pathogenic Enterobacterecea (Musgrove et al, 2008). Some species of Enterobacter have also been isolated from patients' cerebrospinal fluid (Parodi et al, 2003).…”
Section: Hafnia Alveimentioning
confidence: 99%
“…Likewise, Enterobacter species have been reported to cause disease in poultry (Nandi et al, 2013), it has also been isolated form egg shell of poultry together with other pathogenic Enterobacterecea (Musgrove et al, 2008). Some species of Enterobacter have also been isolated from patients' cerebrospinal fluid (Parodi et al, 2003).…”
Section: Hafnia Alveimentioning
confidence: 99%
“…14,19 The predominant antibiotic regimen was defined as the antibiotic used for at least two-thirds of the patient's treatment course. 14 Clinical outcomes were determined by the GCS change and mortality.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…There were only case reports in patients with a history of head trauma, neurosurgical procedures, mastoiditis or chronic sinusitis. 9e13 Prosthetic devices, including external cerebrospinal fluid (CSF) drainage catheters 14 and ventriculoperitoneal (VP) shunts, 11,15 facilitate bacterial colonization and provide a potential route into the CNS, eventually causing meningitis. The use of external ventricular drains (EVDs) or VP shunts might develop an environment associated with a relatively high risk for postneurosurgical CNS infections.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies have demonstrated Streptococcus pneumonia is the most common pathogen in post-surgical meningitis [6] , however the incidence of S. pneumonia observed more in the children [12] . Parodi and co-workers reported that the proportion of cases of nosocomial meningitis due to gram-negative organisms appears to be increasing, they revealed the entrobacters grew rapidly as the cause of nosocomial meningitis [11] . This study expressed our finding to Klebsiella.…”
Section: Discussionmentioning
confidence: 99%